Safe Handover : Safe Patients - The Electronic Handover System. Issue 2 (26th February 2014) - Till, Alex; Sall, Hanish; Wilkinson, Jonathan
Abstract: Failure of effective handover is a major preventable cause of patient harm. We aimed to promote accurate recording of high-quality clinical information using an Electronic Handover System (EHS) that would contribute to a sustainable improvement in effective patient care and safety. Within our hospital the human factors associated with poor communication were compromising patient care and unnecessarily increasing the workload of staff due to the poor quality of handovers. Only half of handovers were understood by the doctors expected to complete them, and more than half of our medical staff felt it posed a risk to patient safety. We created a standardised proforma for handovers that contained specific sub-headings, re-classified patient risk assessments, and aided escalation of care by adding prompts for verbal handover. Sources of miscommunication were removed, accountability for handovers provided, and tasks were re-organised to reduce the workload of staff. Long-term, three-month data showed that each sub-heading achieved at least 80% compliance (an average improvement of approximately 40% for the overall quality of handovers). This translated into 91% of handovers being subjectively clear to junior doctors. 87% of medical staff felt we had reduced a risk to patient safety and 80% felt it increased continuity of care. Without guidance, doctors omit key information required for effective handover. All organisations should consider implementing an electronic handover system as a viable, sustainable and safe solution to handover of care that allows patient safety to remain at the heart of the NHS.